1995
DOI: 10.1074/jbc.270.41.23934
|View full text |Cite
|
Sign up to set email alerts
|

Rho Family GTPases Regulate p38 Mitogen-activated Protein Kinase through the Downstream Mediator Pak1

Abstract: The stress-activated p38 mitogen-activated protein (MAP) kinase defines a subgroup of the mammalian MAP kinases that appear to play a key role in regulating inflammatory responses. Co-expression of constitutively active forms of Rac and Cdc42 leads to activation of p38 while dominant negative Rac and Cdc42 inhibit the ability of interleukin-1 to increase p38 activity. p21-activated kinase 1 (Pak1) is a potential mediator of Rac/ Cdc42 signaling, and we observe that Pak1 stimulates p38 activity. A dominant nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
576
5
1

Year Published

1997
1997
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 706 publications
(610 citation statements)
references
References 25 publications
26
576
5
1
Order By: Relevance
“…A strict requirement for the Rho family of GTPases in Gas6-mediated survival, as analysed with dominant negative constructs, supported the evidence for a speci®c Gas6-survival pathway departing from PI3K. This was further con®rmed by the complete abrogation of Gas6-induced survival through overexpression of a dominant negative Pak, a known downstream Rac/Cdc42Hs molecular target (Zhang et al, 1995). Since RhoA neither activate any known MAPK cascade pathway in mammalian cells nor interact with Pak (Minden and Karin, 1997;Ridley, 1996), we can hypothesize that the block of Gas6 cell survival activity by N17RhoA expression could be mediated through a di erent, Gas6-dependent, signalling pathway possibly involving the Rho-interacting kinase PKN or the phosphoinositide 5-kinase (PI5K) (Symons, 1996).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…A strict requirement for the Rho family of GTPases in Gas6-mediated survival, as analysed with dominant negative constructs, supported the evidence for a speci®c Gas6-survival pathway departing from PI3K. This was further con®rmed by the complete abrogation of Gas6-induced survival through overexpression of a dominant negative Pak, a known downstream Rac/Cdc42Hs molecular target (Zhang et al, 1995). Since RhoA neither activate any known MAPK cascade pathway in mammalian cells nor interact with Pak (Minden and Karin, 1997;Ridley, 1996), we can hypothesize that the block of Gas6 cell survival activity by N17RhoA expression could be mediated through a di erent, Gas6-dependent, signalling pathway possibly involving the Rho-interacting kinase PKN or the phosphoinositide 5-kinase (PI5K) (Symons, 1996).…”
Section: Discussionsupporting
confidence: 53%
“…Pak has been reported to bind Rac/ Cdc42 in a GTP-dependent manner thus mediating their speci®c responses (Symons, 1996;Van Aelst and D'Souza-Schorey, 1997). A Pak cDNA containing a point mutation rendering the enzyme catalytically inactive (Pak K-), thereby behaving as a dominant negative in vivo (Zhang et al, 1995), was co-injected with TrR into the nuclei of quiescent NIH3T3 cells. After 3 h cell death was induced by changing the medium to serum-free medium, with either Gas6 (400 ng/ml) or serum (10%), being separately added as survival factors.…”
Section: Involvement Of Rac and Rho In Gas6-dependent Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylated and stimulated MEKK activate the dual speci®city kinase MKK4 through Ser/Thr phosphorylation (Figure 1). Since MEKK1 can activate both MKK3 and MKK4, it has been observed that interfering the signaling pathway upstream of MEKK1 or MEKK1 itself inhibits the activation of both MKK3-p38MAPK and MKK4-JNK pathways (Yan et al, 1994;Lin et al, 1995;Derijard et al, 1995;Zhang et al, 1995).…”
Section: Map Kinase Kinase-4mentioning
confidence: 99%
“…It has been shown that activation of Rho proteins are also necessary for cell proliferation (Hirai et al, 1997;Hill et al, 1995;Joneson and Bar-Sagi, 1998;Olson et al, 1998). These proteins have also been found to activate the JNK/SAPK signaling pathway in a celltype speci®c manner (Zhang et al, 1995;Coso et al, 1995;Teramoto et al, 1996).…”
Section: Introductionmentioning
confidence: 99%